The Effect of Clove Agricultural Products on Family Welfare Level in Bontobangun Village, Bulukumba Regency - Kumala, Nur; Yanti, Jeddah; Baharuddin, Ichsan Invanni; Alonge, Titus Adeyemi (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2025)
This quantitative descriptive study aims to determine how much influence clove agricultural products have on the level of family welfare in Bontobangun Village, Rilau Ale District, Bulukumba Regency. The independent variable in this study is the agricultural yield of cloves, while the dependent variable is the level of family welfare. The population in this study was all heads of families in Bontobangun Village, Bulukumba Regency, while the sample of this study was 89 households, a sampling technique using proportional random sampling. This study uses data collection techniques through observation, interviews, distribution of questionnaire sheets and documentation. Furthermore, the data is processed using SPSS version 22 and then presented as a table with an explanation. The results showed that the clove farmers’ results significant influenced the family welfare level in Bontobangun Village, Bulukumba Regency. The largest number of clove farmer family members is 46.0 percent who have 3-4 dependents and the lowest number of family members is 10.1 percent who have 7 to 8 dependents. Most clove farming families in Bontobangun Village, Bulukumba Regency, have reached the third-class prosperous family stage. Compulsory needs of family members such as food, clothing, education, and health, family members are dependents.